Strategi Pengembangan Usaha Batik Tulis Lasem Dengan Analisis SWOT - Muhammad Tahwin; A. Aviv Mahmudi (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2014)
This study aims to formulate the developing strategy alternative implemented in Batik Tulis Lasem enterprises. Data analysis used is SWOT Analysis. SWOT matrix result shows that developing strategy for Batik Tulis Lasem industry is SO strategy (agresive strategy), the strategy that uses strength to make use the available opportunity. This strategy implemented marketing line development by exploiting networking, developing quality control and improving productivity using modern technology.